Axially chiral 1, 1′-bicarbazolyls with near-ultraviolet circularly polarized luminescence. Issue 31 (29th March 2022) - Shikita, So; Harada, Takunori; Yasuda, Takuma
Abstract : A novel family of circularly polarized luminescence materials featuring axially chiral 1, 1′-bicarbazolyls was developed, and their photophysical and chiroptical properties were investigated. Abstract : The facile synthesis and chiroptical properties of a new family of circularly polarized luminescence (CPL) materials, axially chiral 1, 1′-bicarbazolyls (BiCz), are reported. The BiCz derivatives emitted intense near-ultraviolet photoluminescence, with a peak at ∼380 nm. The BiCz enantiomers showed mirror-image circular dichroism and CPL, with g lum values on the order of 10 −4 in solution.